Effect of waste polyethylene terephthalate content on the durability and mechanical properties of composites with tire rubber matrix. (February 2017) - Cosnita, Mihaela; Cazan, Cristina; Duta, Anca
The paper investigates new composites fully based on wastes of polyethylene terephthalate, rubber, high-density polyethylene, and wood, aiming at multifunctional, environmental-friendly materials, for indoor and outdoor applications. The rubber: polyethylene terephthalate: high-density polyethylene: wood ratio and compression molding temperatures are optimized considering the output mechanical properties, focusing on increasing the waste polyethylene terephthalate content. To investigate the durability in the working conditions, the water-stable composites, with good tensile and compression strengths were exposed to surfactant systems, saline aerosols, and ultraviolet radiations. The results prove that surfactant immersion improves the interfaces and the mechanical properties and a pre-conditioning step involving the dodecyltrimethylammonium bromide surfactant is recommended, prior application. The interfaces and the bulk composites were investigated by X-ray diffraction, Fourier-transform infrared, differential scanning calorimetry, contact angle measurements, scanning electron microscopy, atomic force microscopy, to identify the properties that influence the mechanical behavior and durability. The composites containing 30% of polyethylene terephthalate, obtained at 160℃ and 190℃ have a good combination of mechanical properties and durability that is enhanced by the plasticizing effect of water and surfactants. The compressive strength of the composite processed at 190℃ was 51.2 MPa and the value increased to 58.4 MPa after water immersion. The ultraviolet and saline exposure slightly diminished this effect; however, long time testing (120 h) ended up with values higher than those corresponding to the pristine composite: 55.3 MPa after ultraviolet and 57.1 MPa after saline exposure.